Is There an Anticorruption Agenda in Utilities? - Kenny, Charles (2012)
In a networked utility setting (few, predominantly monopoly providers), it is very hard to measure the extent of grand corruption using perceptions or surveys. It is even harder to measure the extent of damage done specifically by corruption, petty or grand. As a result, it will be hard to develop "actionable indicators" of, or to develop empirically tested responses to, corruption in utilities. How much does this matter? Corruption is the result of a failure of governance. We can measure the impact of poor governance at the level of the utility, and we have a number of tools to improve their governance. It is not clear that, at the sectoral or company level, there is a significant anticorruption agenda not encompassed by this broader agenda of improved governance. To that extent, the "new" anticorruption agenda provides renewed justification for the "old" focus on institutions at the level of utilities management, but does not require a radically different approach.